1991
DOI: 10.1104/pp.95.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Ovules as Models for Cotton Fiber Development under Low Temperatures

Abstract: Cotton fibers (Gossypium hirsutum L.) developing in vitro responded to cyclic temperature change similarly to those of fieldgrown plants under diumal temperature fluctuations. Absolute temperatures and rates of temperature change were similar under both conditions. In vitro fibers exhibited a "growth ring" for each time the temperature cycled to 22 or 150C. Rings were rarely detected when the low point was 280C. The rings seemed to correspond to alternating regions of high and low cellulose accumulation. Fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 21 publications
2
32
2
Order By: Relevance
“…Ovules of G. hirsutum Acala SJ-1 were cultured in vitro until days 18-21 of fiber development at 34°C as described (21). Western blot analysis of proteins from cultured fibers showed a specific reaction of anti-SuSy antibody, but not preimmune serum, with one polypeptide as did proteins from plant-grown fibers (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Ovules of G. hirsutum Acala SJ-1 were cultured in vitro until days 18-21 of fiber development at 34°C as described (21). Western blot analysis of proteins from cultured fibers showed a specific reaction of anti-SuSy antibody, but not preimmune serum, with one polypeptide as did proteins from plant-grown fibers (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Ovules from cotton (Gossypium hirsutum L. cv Acala SJ1) ovaries harvested 1 d after flower opening were used for the preparation of floating ovule cultures as previously described (17). To reduce variability between replicate observations, ovules from different ovaries and locules were randomized in culture vessels.…”
Section: Cotton Ovule Culturementioning
confidence: 99%
“…Fiber development is typically divided into two stages, primary wall formation (to accomplish elongation) and secondary wall synthesis (to accomplish fiber thickening) (24 Current address: University of Iowa, Ames, IA. lose in the secondary wall that is required for fiber maturation (10,17), and temperatures less than 250C are low enough to induce resistance to the deleterious effects of subsequent exposure to 50C in cotton seedlings (20). The research reported here is focused on the period of secondary wall deposition because of the adverse effect of cool night temperatures in northern cotton growing regions on fiber cell wall thickening, which is a major determinant of crop quality and value (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in my home state of Texas, the quality of the cotton crop often is decreased when grown under cool night temperatures [37]. Regulating ®ber production and quality when plants are grown under stress conditions could signi®cantly improve the economics of cotton production.…”
Section: What Does the Future Hold?ðbiotechnology Implicationsmentioning
confidence: 99%